Toxic effects of waterborne cadmium exposure on hematological parameters, oxidative stress, neurotoxicity, and heat shock protein 70 in juvenile olive flounder, Paralichthysolivaceus. Issue 122 (March 2022) - Lee, Deok-Chan; Choi, Young Jae; Kim, Jun-Hwan
Abstract: Cadmium-induced toxicity can affect fish embryo development, ion homeostasis regulation, energy metabolism, maturation and growth, stress response, and immunity. However, studies on the toxic effects of cadmium exposure to aquatic animals, particularly olive flounder ( Paralichthys olivaceus ), are limited. In this study, juvenile P. olivaceus (mean length, 12.9 ± 1.3 cm; mean weight, 23.1 ± 3.2 g) was exposed to waterborne cadmium (0, 50, 100, 200, and 400 μg/L) for 10 d. Hematological parameters, including hematocrit value and hemoglobin level, in P. olivaceus were significantly decreased after waterborne cadmium exposure. Plasma components such as calcium, glucose, cholesterol, glutamic-oxaloacetic transaminase, and glutamic-pyruvic transaminase were significantly altered via cadmium exposure. The activities of antioxidant enzymes, such as superoxide dismutase, catalase, and glutathione S-transferase, were significantly altered in P. olivaceus after cadmium exposure. Acetylcholinesterase activity was significantly inhibited upon waterborne cadmium exposure. Hepatic heat shock protein 70 was significantly upregulated in P. olivaceus after waterborne cadmium exposure. Therefore, waterborne cadmium at concentrations of >100 or 200 μg/L can induce physiological toxicity in P. olivaceus via changes in hematological parameters, antioxidant enzymes, neurotransmitters, and stress indicators. Graphical abstract: Image 1 Highlights: Hematological parameters of the P. olivaceus were significantly decreased by cadmium exposure. Plasma components of the P. olivaceus were significantly changed by cadmium exposure. Waterborne cadmium exposure affected antioxidant responses of the P. olivaceus. The AChE and HSP 70 of the P. olivaceus were significantly affected by cadmium exposure. Cadmium exposure more than 100 or 200 μg/L were significantly affected as toxicity.